Unique topological motifs in two Cd(ii)-coordination polymers: mutual-embedded 2D bilayers, 3D polythreaded structures, self-penetrated networks and 2D → 2D interpenetrated homochiral bilayers. Issue 47 (2nd November 2015) - Xu, Guo-Wang; Wu, Ya-Pan; Wang, Hai-Bing; Wang, Ye-Nan; Li, Dong-Sheng; Liu, Yun-Ling
Abstract : Two unique entangled Cd(ii ) coordination polymers have been modulated by flexible/semi-rigid mixed-ligand systems. Abstract : Two unique entangled Cd(ii ) coordination polymers, {[Cd2 ( m -pdoa)2 (dpa)3 (H2 O)]} n (1 ) and {[Cd( m -pdoa)(bpp) (H2 O)]·2H2 O} n (2 ) ( m -H2 pdoa = 1, 3-phenylenedioxy diacetic acid, dpa = 4, 4′-dipyridylamine; bpp = 1, 3-di(4-pyridyl)propane), have been modulated using flexible/semi-rigid mixed aromatic carboxylate and pyridine derivative ligands and characterized using elemental analysis, infrared spectra (IR), powder X-ray diffraction (PXRD) and single-crystal X-ray diffraction.1 shows the first topological motifs of mutual-embedded bilayers originating from two reverse 2D 4 4 - sql layers with 1D single side arms in an alternating fashion, and thus affording a 3D polythreaded structure featuring poly-pseudo-rotaxane that exhibits a new 3D (3, 3, 3, 3, 3, 5, 5, 5)-connected self-penetrated H-bonding net. Whereas2 displays rare 2D → 2D homochiral interpenetrated layers propagating from 4 4 - sql chiral layers. Additionally, thermal stabilities and luminescent properties for1 and2 were also discussed.